2017
DOI: 10.1111/andr.12389
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphology: assessment, pathophysiology, clinical relevance, and state of the art in 2017

Abstract: For over 30 years, sperm morphology assessment has been one of the most common tests in evaluation of fertility. This review examines the clinical relevance of sperm morphology assessment in the diagnosis of infertility and in assisted reproductive technology, as well as its analytical reliability. Publications on the pathophysiology, the analytical reliability of the test and its clinical relevance in diagnosis and in Assisted Reproductive Technology (ART) were evaluated. This review compared and discussed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 204 publications
0
79
0
2
Order By: Relevance
“…It is well known that under conditions of real space flight and various microgravity models, oxidative stress occurs due to the accumulation of reactive oxygen species and nitrogen oxide [51]. In turn, oxidative stress is one of the most well-studied factors leading to chromatin damage in spermatozoa [52,53], especially if the hormone concentrations are stable, there is a lack of toxic effects, and so on. Nevertheless, we did not observe a redistribution of morphological abnormalities after suspension, and the proportion of spermatozoa with an abnormal head did not differ in all study groups.…”
Section: Sperm-specific Proteins and Their Expression Levelsmentioning
confidence: 99%
“…It is well known that under conditions of real space flight and various microgravity models, oxidative stress occurs due to the accumulation of reactive oxygen species and nitrogen oxide [51]. In turn, oxidative stress is one of the most well-studied factors leading to chromatin damage in spermatozoa [52,53], especially if the hormone concentrations are stable, there is a lack of toxic effects, and so on. Nevertheless, we did not observe a redistribution of morphological abnormalities after suspension, and the proportion of spermatozoa with an abnormal head did not differ in all study groups.…”
Section: Sperm-specific Proteins and Their Expression Levelsmentioning
confidence: 99%
“…The questionnaire results confirm this hypothesis: Only half of the laboratories perform sperm morphology assessment of which only two use the Papanicolaou stain, as described by the WHO. A similar result was found in France (Gatimel et al ., ). The risk of not performing sperm morphology assessment is complex to speculate about, as on the one hand, one might miss specific severe abnormalities which lead to infertility (e.g., globozoospermia, 100% short motile tails, 100% severe ERC, and 100% stress‐induced elongated sperm heads) and, on the other hand, a poor performance may lead to unsuitability of the algorithm used for patient selection.…”
Section: Discussion With Conclusionmentioning
confidence: 97%
“…Morphology is a parameter subjected to strong inter‐laboratory variations, so much so that some consider it to be one of the most subjective parameters in sperm testing (Punjabi et al, ) and moreover some question its relevance (Gatimel, Moreau, Parinaud, & Léandri, ). Authors revealed that classification changes and standard modifications inside the successive editions of the WHO classification all played a part in keeping this parameter in blurred territory.…”
Section: Discussionmentioning
confidence: 99%